PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PROFITABILITAS MELALUI STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN ASURANSI DI BURSA EFEK INDONESIA PADA TAHUN 2019-2022 - Istifani, Shofiatul Hasana Nur; Wahyuni, Ika; Widaninggar, Nanda (Fakultas Ekonomi dan Bisnis, 2024)
Insurance companies are growing along with the development of the business world. Whatever form or type of economic business is running, it is not only about financial benefits but also the risk of damage and bankruptcy. Human activities are increasingly diverse daily. Therefore some people need insurance while others do not. The human need for insurance encourages insurance companies to compete to get customers. This study analyzes the effect of Managerial Ownership Structure, Company Size, and Leverage on Profitability through Capital Structure as an intervening variable. The method used in this study is quantitative. The population in this study are insurance companies listed on the Indonesia Stock Exchange in 2019-2022. Purposive sampling is the sampling technique in this study. Data analysis and hypothesis testing in this study use the Structural Equation Model. The results of the hypothesis test using a statistical application, namely Smart PLS 3.0, show that the managerial ownership structure has a significant negative effect on capital structure, company size has a significant negative effect on capital structure, leverage has a significant positive effect on capital structure, managerial ownership structure has a positive but insignificant effect on profitability, company size has a positive but insignificant effect on profitability, leverage has a positive but insignificant effect on profitability, capital structure has a negative but insignificant effect on profitability, managerial ownership structure has a positive but insignificant effect on profitability through capital structure, company size has a positive but insignificant effect on profitability through capital structure, leverage has a significant negative effect on profitability through capital structure.